Factors Influencing the Behavioural Intention of Buyers Towards Bajaj Pulsar Bike: A Comparative Study in India And Ethiopia - , DR.D.BARANIKUMAR; SHOBANA, DR.R.; UDO, MR. MANDHO GENALE (The journal of contemporary issues in business and government, 2021)
An attitude is a learned proclivity to act consistently in a favourable or unfavourable manner toward a specific object. From time to time, consumer attitudes will change. Various models assist us in determining the consumer's attitude. In general, satisfaction refers to a person's feelings of delight or dissatisfaction as a result of contrasting a product's perceived results to his or her expectations. The customer is disappointed because the result falls short of expectations. Customers' needs change over time. For a period of time, the attractive and even unexpected attributes offered by competitors may become important attributes as consumers begin to expect them. A customer's sense of awareness and realization regarding a business or its contributions is referred to as consumer experience in marketing. The researcher has used the descriptive design for this current study. For the Primary data`s 110 sample size was taken randomly (Google form). For this study three factors are taken into consideration. Those are social, psychological, and personal factors. The hypothesis was framed and Statistical tools like numerical wrap up for societal science (SPSS) test were worn. By this study, a researcher was able to find out that the opinion of the middle income group about the prestige, stylish and comfortable and opinion about brand image, durability, dream vehicle, eco friendly, technically sound are significantly high. The study revealed that brand name and the power the bike are important reasons to choose the bike from both countries